Service of letters abroad in the administrative and court proceedings - Lewicka, Renata (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The issues connected with service of letters in the administrative and court proceedings beyond the Republic of Poland under the European Union law and particularly under the case law of the Court of Justice, establishing standards of the letter service become more and more important. The source of significant practical problems is the fact that there are no regulations concerning the service of letters in general administrative proceedings both between the EU states (with the exception of tax and customs issues which are regulated) and to the states which are not members of the European Union. Apart from a classic way of serving a letter upon somebody by a postal operator which is unfortunately not always effective, some other ways of service are applied in an auxiliary way. However, it must be noted that there are no regulations normalizing consistently methods of a letter service in arious types of the proceedings which leads to unjustified diversity in standards in the range of serving letters depending on a subject matter of the proceedings.